La participación de la familia en el proceso educativo de la Escuela E.G.B. Riobamba - Paste Guanoluisa, Daysi Magaly (2020)
The research work has been proposed due to the need to address the problem of how to improve the family’s participation in the educational process of the E.G.B. Riobamba school, for which a general objective has been established, to develop a family participation programmer that will improve the action of the parents around their relationship with the educational institution and their environment. The methodology used in the research is based on the guidelines of the qualitative paradigm, since the aim is precisely to generate actions that will improve family participation in the educational process. The research method is as basic as the applied one; as far as methods are concerned, we have worked with the deductive method to construct and systematize the theoretical framework. Once all the phases or stages proposed have been completed, the conclusion has been reached that the family's participation in their children's education is deficient or non-existent, which prevents adequate coordination and therefore the achievement of optimum results at each of the levels.